2020
DOI: 10.3390/catal10020151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of KCoMoS2 Catalyst Structures on the Catalytic Performance of Higher Alcohols Synthesis via CO Hydrogenation

Abstract: Different structures of cobalt and potassium modified molybdenum sulfide catalyst (KCoMoS2) were synthesized by hydrothermal synthesis, coprecipitation and reverse microemulsion methods. Nitrogen adsorption, XRD, TEM, XPS and HAADF-STEM-EDS techniques were used to characterize the catalysts structures. The results indicate that the molybdenum sulfide-based catalyst synthesized by the reverse microemulsion method possessed less sheets with small lateral dimensions, while the catalysts prepared by the former two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(51 reference statements)
2
1
0
Order By: Relevance
“…The results reported in Figure c emphasize the results reported by Liu et al and Qin et al: a negative correlation between small average crystallite length ( L̅ < 6 nm) and CO conversion was reported, but the yield of hydrocarbons was relatively higher compared with other catalysts. Altogether, HAS progresses not only via carbon monoxide insertion but also via aldol condensation of shorter alcohols …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The results reported in Figure c emphasize the results reported by Liu et al and Qin et al: a negative correlation between small average crystallite length ( L̅ < 6 nm) and CO conversion was reported, but the yield of hydrocarbons was relatively higher compared with other catalysts. Altogether, HAS progresses not only via carbon monoxide insertion but also via aldol condensation of shorter alcohols …”
Section: Resultssupporting
confidence: 88%
“…Based on the described model, the performance of different active sites on the bulk MoS 2based catalysts for production of hydrocarbons increased in the order basal sites ≪ edge sites < rim sites. They reported that The results reported in Figure 10c emphasize the results reported by Liu et al 70 and Qin et al: 71 a negative correlation between small average crystallite length (L̅ < 6 nm) and CO conversion was reported, but the yield of hydrocarbons was relatively higher compared with other catalysts. Altogether, HAS progresses not only via carbon monoxide insertion but also via aldol condensation of shorter alcohols.…”
Section: Catalytic Conversion Ofsupporting
confidence: 81%
See 1 more Smart Citation